(3ZQQ GdahGFO hOQQ GdbdGFOs - (3GdTQja GdeQJVj , CHh GdbGSe,J (B436 (3g` s
(3ChdgG (B:s
(3bGd GdTQja GdeQJVi bOS Gddg QhMg Ef SCd SGFd Yf bhd Gddg JYGdi (B" (3hEPG CQOfG Cf fgdc bQjI CeQfG eJQajgG aaSbhG ajgG aMb YdjgG Gdbhd aOeQfGgG JOejQkG (B" s
(3BNQgG (B:s
(3gPG BNQ eLdS CedGg SjOfG COGe Gddg Ydhg Ke JTGZd HCeQh GdML GdMeO ddg QH GdYGdejf hUdhGJg Ydi SjOfG eMeO hBdg GdWjHjf GdWGgQjf hSde cKjQG s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ HGdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B278 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd s
Keywords: (3GdJhMjO hGdedd hGdfMds